2020
DOI: 10.1016/j.btre.2019.e00409
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability potentials of novel laccase tinctures from Stenotrophomonas maltophilia BIJ16 and Bordetella bronchiseptica HSO16: From dye decolourization to denim bioscouring

Abstract: HighlightsLaccase from Hb16c and Berl11b2 exhibited remarkable polyextremotolerant properties.A novel high concentration of synthetic dyes was efficiently degraded.Bioscouring of denim was achieved by a mediator-associated laccase treatment.Multiple laccase-encoding genes were observed in a laccase-producing strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…S maltophilia BM produce laccase enzymes maximally at pH 7. This result is in accordance with the research conducted by Unuofin (2020) which reported that the optimum pH of Stenotrophomonas maltophilia BIJ16 to produce laccase enzymes was 7.0.…”
Section: Resultssupporting
confidence: 93%
“…S maltophilia BM produce laccase enzymes maximally at pH 7. This result is in accordance with the research conducted by Unuofin (2020) which reported that the optimum pH of Stenotrophomonas maltophilia BIJ16 to produce laccase enzymes was 7.0.…”
Section: Resultssupporting
confidence: 93%
“…Unuofin et al (2019) opine that the exact function of all the bacterial laccase genes discovered so far has not been ascertained; however, they have been linked with resistance to radiation and synthesis of pigments. There is a connection between laccase activity induction and bacterial dye decolorization (Lee et al 1994;Ayed et al 2010;Unuofin 2020). The earlier report is available related to the copper depended on an enzyme, multicopper oxidase in Stenotrophomonas maltophilia coded by cop A gene which has laccase activity, copper resistance and in vitro dye decolorization property (Galai et al 2011).…”
Section: Molecular Snapshot Of Bacterial Isolate For 'Lac' and 'Tmr' Genesmentioning
confidence: 99%
“…They produce laccase, which can degrade colors by dissolving their reactive groups. To increase degradation efficiency, sequential treatment approaches have been studied in which reactive dyes are first adsorbed onto a solid substrate and then subjected to enzymatic degradation by WRF (Unuofin, 2020). To increase the breakdown of reactive dyes, combination treatments using WRF and other microorganisms such as bacteria or yeasts have been researched.…”
Section: The Ability Of Wrf To Degrade Various Classes Of Textile Dye...mentioning
confidence: 99%